Energy and Environment for Smart Cities: Life Sciences-Environment - Dr. Pankaj Kumar Mishra, Editor-in-Chief (International Journal of Life Science and Pharma Research, 2018)
Wireless sensor networks (WSNs) are combination of distributed independent devices. It uses sensors to cooperatively monitor environmental or physical circumstance like pressure, temperature, voice, vibration, motions at different locations. Wireless sensor networks are networks in which the numbers of sensor nodes are connected to each other. They send the data to base station which is gathered from the field. Actually this data is sent to the BS in multi hop process so a number of sensors are connected and perform task. The fields of energy efficient routing protocols in the Wireless sensor networks are considered too much for doing research that’s why this paper presents an overview of the hierarchical based routing protocols in the field of wireless sensor networks. In the field of WSNs the numbers of routing protocols are working. The broadly used routing protocols are clustering based routing protocol because the data is transferred from one node to another or also from one node to BS. Data is transferred in a multi hop not in a single hop. The shared nature of wireless sensors networks makes energy efficient protocol .This design is peculiarly difficult. The unique problems are self-configurable, multi-hop routing cross layer, medium access control. Network discovery design is necessary to come up about energy efficient and constant solutions. Thus cluster network will be used for measuring soil parameters such as moisture, temperature, humidity etc. All the countries realize that wireless sensor networks are most advance technology for the progress of the country in all areas. This paper particularly presents the survey on energy efficiency routing protocols in the field of agriculture using wireless sensor networks.